MRI data compression using a 3-D discrete wavelet transform. - Badawy, W.
A low-power system that can be used to compress MRI data and for other medical applications is described. The system uses a low power 3-D DWT processor based on a centralized control unit architecture. The simulation results show the efficiency of the wavelet processor. The prototype processor consumes 0.5 W with total delay of 91.65 ns. The processor operates at a maximum frequency of 272 MHz. The prototype processor uses 16-bit adder, 16-bit Booth multiplier, and 1 kB cache with a maximum of 64-bit data bandwidth. Lower power has been achieved by using low-power building blocks and the minimal number of computational units with high throughput.
Keywords: 0.5 W; 1 kB cache; 16-bit Booth multiplier; 16-bit adder; 272 MHz; 3-D discrete wavelet transform; 64-bit data bandwidth; 91.65 ns; MRI data compression; Centralized control unit architecture; Low-power building blocks; Magnetic resonance imaging; Medical diagnostic imaging